Examining self-monitoring as a moderator of the effectiveness of social norms and self-schema matched messages for reducing binge drinking among college students - Miller, Megan Michelle (Kansas State University, 2009)
Self-monitoring was examined as a moderator of the effectiveness of persuasive messages for reducing college student binge drinking. Low self-monitors tend to be influenced by their personal values and attitudes, while high self-monitors tend to be influenced by the behavior of those around them. Via a website simulation, college students were presented with one of three types of anti-binge drinking messages: a self-schema message, which highlighted how responsible drinking is consistent with the message recipient’s personal values and attitudes; a social norms message, which explained that most college students drink less than one might think they do; or a control message, which stated in general terms that people can experience a variety of problems from binge drinking. Overall intended drinking behavior in the self-schema message condition was almost identical to that of the social norms message condition, both of which were lower than drinking intentions in the control message condition. When presented with a self-schema matched message, low self-monitors intended to drink less alcohol than did high self-monitors, but these means were not significantly different. However, high self-monitors intended to drink significantly less than did low self-monitors when presented with a social norms message. The results suggest that self-schema matched messages may be effective at reducing binge drinking for most students, and that social norms messages may be equally as effective but only for high self-monitors.
Keywords: Binge drinking; Persuasive messages; Self-monitoring; Social norms; Self-schema; Psychology, Social (0451)